Corporate Enviropreneurship: Greening the Pricing and Promotion Practices of Polythene Manufacturing Companies for Consumer Sustainability in Nigeria - Abanyam, Friday Ekahe; Igu, Faith Ogochukwu; Ibelegbu, Anthonia Ngozi; Nyaro, Margaret Andrew; Abanyam, Victor Attah (International Business Education Journal, 2023)
The study focused on corporate enviropreneurship, with the specific objective of determining the green pricing and promotion practices for polythene companies to achieve sustainable consumption in Nigeria. The embedded type of mixed method research design was adopted for the study which 323 respondents, comprising of 35 marketing lecturers, 60 managers of polythene manufacturing companies, and 223 polythene consumers in Nigeria were used to collect data. Questionnaire and focus group discussion were the instruments employed to gather data, which were validated by five experts. Cronbach Alpha reliability method was used to determine the internal consistency of the questionnaire. The overall reliability index for the instrument was 0.89. The collected data were analyzed using mean, standard deviation and analysis of variance statistics. The study found 18 green pricing and 18 promotion frameworks that are highly essential for polythene companies to achieve sustainable consumption practices. Based on the findings of the study, it was concluded that the adoption of green pricing and promotion practices by polythene companies would ensure sustainable consumption in Nigeria. It was recommended, among others, that polythene manufacturing companies adopt green pricing and promotion practices to achieve consumer and environmental sustainability.